From Cerebellar Activation and Connectivity to Cognition: A Review of the Quadrato Motor Training - Ben-Soussan, Tal Dotan (Biomed Res Int, 2015)
The importance of the cerebellum is increasingly recognized, not only in motor control but also in cognitive learning and function. Nevertheless, the relationship between training-induced cerebellar activation and electrophysiological and structural changes in humans has yet to be established. In the current paper, we suggest a general model tying cerebellar function to cognitive improvement, via neuronal synchronization, as well as biochemical and anatomical changes. We then suggest that sensorimotor training provides an optimal paradigm to test the proposed model and review supporting evidence of Quadrato Motor Training (QMT), a sensorimotor training aimed at increasing attention and coordination. Subsequently, we discuss the possible mechanisms through which QMT may exert its beneficial effects on cognition (e.g., increased creativity, reflectivity, and reading), focusing on cerebellar alpha activity as a possible mediating mechanism allowing cognitive improvement, molecular and anatomical changes. Using the example of QMT research, this paper emphasizes the importance of investigating whole-body sensorimotor training paradigms utilizing a multidisciplinary approach and its implications to healthy brain development.